The estimation of errors in calculated terrain corrections in the Tatra Mountains - ZAHOREC, Pavol; PAŠTEKA, Roman; PAPČO, Juraj (Contributions to Geophysics and Geodesy, 2010)
In general, calculation of terrain corrections can be a substantial source oferrors in evaluating Bouguer anomalies, especially in rugged mountainous areas like theTatra Mountains where we also get the largest values of the terrain corrections as such.It is then natural that analysis of their calculations in this area can shed light on themagnitude of correction-related errors within the whole Slovak territory. In the frameworkof our analysis we have estimated the effect of different computing approaches as well asthe influence of accuracy of the inputs, i.e. the heights and positions of the measuringpoints, together with the used digital terrain models. For the sake of testing the computerprograms which are currently in use, we have also substituted the real terrain by synthetictopography. We found that among the concerned constituents the most important factoris the used digital terrain model and its accuracy. The possible model-caused errors canexceed 10 mGal in the Tatra Mountains (for the density of 2.67 g.cm−3).